Russia's heavy fuel oil exports: Challenges and changing rules abroad and at home - Vitaly Yermakov; James Henderson; Bassam Fattouh (The Oxford Institute for Energy Studies, 2019)
The Russian refining system still has a significant legacy from its Soviet past, when refineries were located in relatively remote regions to serve the military and industrial complex and output of fuel oil was encouraged to supply heavy industry. However, this focus on the lower end of the barrel left a significant need for upgrading as Russia entered the post-Soviet era and demand for lighter products increased. The government has tried to provide a series of incentives to encourage Russia's major oil companies to invest in upgrading. Differentiated tax rates, adjust of export tariffs, re-alignment of upstream and downstream taxes and even a command by the then Prime Minister Vladimir Putin that the industry must act to improve its performance have produced some results, particularly since 2015. Since then fuel oil output has declined rapidly, but with demand also falling Russia continues to produce a surplus. Plans for further additions of more complex refining units have been made, thanks to yet more tax incentives, but it would still appear that not all the players will respond as the government hopes. A number of small players may continue to focus on the simpler and less expensive processes, and companies that are the subject of international sanctions have also been given an effective dispensation to slow their upgrading efforts. Many independent refineries are likely to continue using the tactics of selling surrogate refined products without paying excise taxes, to remain afloat. Lower margins for those refineries that are part of Russian vertically integrated companies are likely to be cross-subsidized by profitable upstream operations. Also, the adjustment could take longer than expected due to the social risks of shutting down inefficient facilities. As a result, it would seem that the planned decline in Russian fuel oil output will be at the slow end of the planned range. This is a concern because the global market for fuel oil is set to be further constrained by the introduction of tighter IMO rules on the use of high sulphur fuel oil in the maritime sector from 2020. As shipping companies are forced to use more environmentally friendly fuel and reduce emission, Russian refiners which produce excess fuel oil could find their margins significantly squeezed.
Keywords: 330; Heavy Fuel Oil; IMO 2020; Russian Fuel Oil Exports; Russian Refining Sector